Simplicity : a novel - Lubchansky, Mattie (Pantheon Books, 2025)
"In 1977, a group called The Spiritual Association of Peers decamps to the woods of the Catskills, taking over an abandoned summer camp. They name their new home Simplicity. In 2081, scholar Lucius Pasternak, a fastidiously organized trans man, tries to keep his head down living in the New York City Administrative and Security Territory, which was founded after the formal dissolution of the United States in 2041. Then, he's offered a job by the mayor, billionaire real estate developer Dennis Van Wervel, to complete an anthropological survey of the people of Simplicity for a history museum he's financing. A wary Lucius is nevertheless drawn in by the people of the small wooded community, intrigued by its strange rituals and in particular by the charming acolyte Amity Crown-Shy. Born and raised on the compound, Amity is comfortable in their own skin, a striking contrast to Lucius' repressed reserve. But Lucius' control starts to slip when he begins to suffer visions both terrifying and sensual-visits from beautiful but nightmarish creatures. Then, just as Lucius discovers that Van Wervel's project is more sinister than it seemed, members of the community begin to disappear, leaving behind grisly signs of struggle. The denizens of Simplicity believe that a being they call "The Lamentation" is responsible for the attacks. Amity and Lucius set out to hunt for the creature in the dangerous Exurb Zones, a wild wood full of libertarian doomsday preppers, wealthy isolationists, and worse. There, they'll finally discover the true threat to their way of life-and what they're willing to do to stop it"--